Resilience as a tool for change in order to achieve happiness in adolescents in North Lima - Angeles Donayre , Mariuccia Maisy (2021)
The objective of the study was to describe the levels of resilience in adolescents according to sex and chronological age. The design was non-experimental, cross-sectional; descriptive quantitative type. 515 adolescents aged 10 to 12 participated. The instrument used was the Salgado Personal Resilience Factors Inventory. The results at a general level and in terms of age and sex, the predominant level was the average, followed by the high level. This implies that in the adolescents evaluated, resilience is in full formation, which would be a tool for change in the face of future adverse situations that they may experience. Therefore, much more work must be done at these ages so that this ability can improve cognitively and emotionally and thus improve other aspects of their life, including happiness.